Development and validation of a sensitive LC-MS/MS method for determination of intracellular concentration of fluconazole in Candida albicans - Wang, Xiaofei; Wang, Xiaojuan; Cai, Tongkai; Qin, Yulin; Li, Ling; Jiang, Yuanying; Han, Bing; Cao, Yongbing (Frontiers in Microbiology, 2022)
Systemic candidiasis is the fourth leading cause of healthcare-associated infections worldwide. The combination therapy based on existing antifungal agents is well-established to overcome drug resistance and restore antifungal efficacy against drug-resistant strains. In this study, a simple and sensitive LC-MS/MS method was developed to quantify the intracellular fluconazole (FLC) content in the opportunistic human fungal pathogen Candida albicans. The cell lysates were prepared by lysing C. albicans cells with Precellys homogenizers and FLC was extracted with methylene chloride. The entire extraction approach was simple, precise and reliable. The extracts were separated on a Zorbax SB-C18 column using a mobile phase of acetonitrile (solvent A) and deionized water plus 0.1% formic acid. FLC and ketoconazole (KCZ, internal standard) were monitored in positive mode using electrospray ionization source. The multiple reaction monitoring transitions (precursor to product) were monitored for FLC m/z 307.1 → 238.2 and for the internal standard KCZ m/z 531.2 → 489.1. The linear for this method were in the range from 5.0 ng/mL to 1000.0 ng/mL. The precision and accuracy of the samples were RSD < 1.0% for intra-day and RSD < 0.51% for inter-day. The overall recovery of FLC from samples was higher than 77.61%. Furthermore, this method was successfully applied and validated in 36 clinical isolated strains. Taken together, we established a highly accurate, efficient, and reproducible method for quantifying the intracellular content of FLC in C. albicans.